Combined Effects of Hydrological Drought and Reduced Food Availability on the Decline of the Little Penguins in South Australia - Colombelli-Négrel, Diane; Nur, Darfiana; Auricht, Hannah C. C.; Clarke, Kenneth D.; Mosley, Luke M.; Dann, Peter (Frontiers in Marine Science, 2022)
Droughts in many regions of the world are increasing in frequency and severity which, coupled with effects from anthropogenic water extraction and diversion, are reducing river discharges. Yet to date, few studies have investigated the impacts of hydrological droughts (i.e., reduced river outflows to the ocean) on seabirds. Here, we examined the consequences of the “Millennium Drought” on the local decline of an iconic Australian seabird, the little penguin (Eudyptula minor). We analysed monthly and annual penguin numbers in relation to river outflow, rainfall, the characteristics of the coastal waters (sea surface temperatures and chlorophyll-a concentrations), and local abundance of key predators and prey species. We found a negative association between monthly penguin numbers and both sea surface temperatures and river outflow. Annual penguin numbers were positively associated with southern garfish numbers (our local indicator of food availability) but negatively associated with annual chlorophyll-a concentrations. Our findings emphasizing the need for further research into the effect of hydrological droughts on seabird populations and for improved river management that account for potential downstream impacts on the coastal environment receiving freshwater from rivers.